PENGARUH MODEL PEMBELAJARAN COLLABORATIVE INQUIRY LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI INTERAKSI SOSIAL KELAS VII DI SMP LABSHCOOL UNESA 2 - Cahyu Vita Anggraini (Jurnal Dialektika Pendidikan IPS, 2026)
This study aims to determine the effect of the Collaborative Inquiry Learning model on student learning outcomes and analyze the improvement in student learning outcomes in Social Interaction material for seventh grade students at SMP Labschool Unesa 2 Surabaya. The method used was a quantitative experiment with a Quasi-Experimental design, involving class VII-A as the control and VII-B as the experimental class selected through purposive sampling. Data were collected through tests and documentation, then analyzed using Paired Sample t-tests, Independent Sample t-tests, and N-Gain Scores with SPSS 25. The results showed a significant difference between pretest and posttest scores in the experimental class, with an average N-Gain Score for Collaborative Inquiry Learning being very good at an average percentage of 81.83%. Thus, it can be concluded that the implementation of the Collaborative Inquiry Learning model has a positive and significant effect on improving student learning outcomes in Social Interaction material.